Additional Common Bean in the Diet of Malawian Children Does Not Affect Linear Growth, but Reduces Intestinal Permeability. Issue 2 (27th February 2018) - Agapova, Sophia E; Stephenson, Kevin B; Divala, Oscar; Kaimila, Yankho; Maleta, Kenneth M; Thakwalakwa, Chrissie; Ordiz, M Isabel; Trehan, Indi; Manary, Mark J
Abstract: Background: Chronic malnutrition, as manifested by linear growth faltering, is pervasive among rural African children. Improvements in complementary feeding may decrease the burden of environmental enteric dysfunction (EED) and thus improve growth in children during the critical first 1000 d of development. Objective: We tested the hypothesis that systematically including common bean or cowpea into complementary feeding would reduce EED and growth faltering among children in rural Malawi. Methods: This was a double-blind clinical trial in which children 12–23 mo of age were randomly assigned to receive complementary feeding with 1 of 3 foods: roasted cowpea or common bean flour, or an isoenergetic amount of corn-soy blend as a control food for 48 wk. Children aged 12–23 mo received 155 kcal/d and thereafter until 35 mo received 200 kcal/d. The primary outcomes were change in length-for-age z score (LAZ) and improvements in a biomarker of EED, the percentage of lactulose (%L) excreted as part of the lactulose:mannitol dual-sugar absorption test. Anthropometric measurements and urinary %L excretion were compared between the 2 intervention groups and the control group separately with the use of linear mixed model analyses for repeated measures. Results: A total of 331 children completed the clinical trial. Compliance with the study interventions was excellent, with >90% of the intervention flour consumed as intended. No significant effects on LAZ, change in LAZ, or weight-for-length z score were observed due to either intervention legume, compared to the control. %L was reduced with common bean consumption (effect estimate was –0.07 percentage points of lactulose, P = 0.0007). The lactulose:mannitol test was not affected by the legume intervention. Conclusion: The addition of common bean to complementary feeding of rural Malawian children during the second year of life led to an improvement in a biomarker of gut health, although this did not directly translate into improved linear growth. This trial was registered at clinicaltrials.gov as NCT02472301.